GO-KNO3 fertilizer: Slow release fertilizer innovation from coconut shell waste as a solution to Indonesian food security - Muckharom, Ahmad Ali; Nastiti, Davina Maritza; Qudsiyah, Risma Aimatul; Sutanto, Heri (Journal of Agrosociology and Sustainability, 2025)
Background: As a country with a large agricultural sector, using fertilizers is an essential factor. Inorganic fertilizers such as KNO3 are an option, but excessive use of fertilizers results in the accumulation of inorganic residues. The use of fertilizers that can release controlled nutrients is very necessary, one of which is by encapsulating with Graphene Oxide (GO). Methods: Coconut shell waste is used as the primary material for making GO which is synthesized by the Hummer method with variations in the mass of coconut shell graphite, the characterization of graphene oxide was Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM), and Atomic Absorption Spectrophotometry (AAS). Findings: This research aims to synthesize GO and determine its characteristics as an encapsulation of KNO3 fertilizer. Conclusion: The FTIR results obtained in this research detected O-H bonds, C-H bonds, and C = C bonds. In TEM characterization, thin morphology results were obtained, indicating an oxidation process in the formation of graphene oxide. The AAS showed that the release of KNO3 from graphene oxide was maximum after 8 hours with a percentage of 93.8%. This fertilizer will be used to solve the problem of low plant absorption of macronutrients contained in fertilizers. Novelty/Originality of this article: Encapsulating KNO₃ fertilizer using GO to control nutrient release is a novel approach. This technique addresses the challenge of nutrient overuse and minimizes the environmental impact of inorganic fertilizers.